Reframing the Self in an International Learning Context: The Experience of International Students with Disability - Briony Supple; Joseph Seyram Agbenyega (Arizona State University, 2015)
In teaching and dialoguing with international students with disability we often had to struggle with questions such as: What is the nature of student experience? And how are we supporting international students with disability articulate transformative perspectives of the self? This paper, which is based on a qualitative case study of two international students with a disability at McKenzie University (a pseudonym) Melbourne, Australia, is written to provide insider accounts and provoke understanding into how Bourdieus notion of habitus, capital and field can be expanded to account for the conscious transformations that the students made in recalibrating themselves in their new fields. The paper calls for nuanced reading of how transformation of the self constitutes ongoing reframing of the habitus as a way of detaching oneself from dominant prescriptions of disability within ones field. We ask our readers to consider how this detachment brings into being new formation of the self and capital to the students.  Finally we bring a reflective reading to the data as a critical moment of practice and to reclaim our understandings of disability not as inability, but as complicated socio-political construct that needs to be contested. It is within these contested spaces that we can gain the strength to give marginalized selves the voices they need to move beyond margins of tertiary education.